EFFECT OF IRRIGATION INTERVAL AND SOIL AMENDMENTS ON SOIL ORGANIC C, NITROGEN AND POTASSIUM OF SANDY SOIL AND GROWTH OF Jatropha curcas L. - Djajadi Djajadi; Sulis Nur Hidayati (AGRIVITA Journal of Agricultural Science, 2013)
Inherently, sandy soil is the unfertile soil with low in all aspects of soil fertility and has a low capacity to retain water applied nutrients.  To improve the fertility of sandy soil as media growth of Jatropha curcas, clay and organic matter may have important role when they are incorporated to the sandy soil.  This study investigated the effect of irrigation interval and incorporation of clay together with organic matter to sandy soil on soil organic C, N, and K and growth of J. curcas.  The rates of clay and organic matter incorporated to top sandy soil were 5% clay + 0.8% organic matter and 10% clay + 1.6% organic matter. Two irrigation intervals tested were 10 day and 20 day.  The results found that incorporation of 10% clay + 1.6% organic matter to sandy soil increased soil C organic, N total and exchangeable K which in turn increased number of leaves and number of lateral branches of J curcas.  Irrigation intervals had no effect on all parameters observed.Key words: Jatropha curcas, C organic, Nitrogen, Potassium, clay, organic matter, irrigation interval, plant growth